Analisis Butir Soal Ranah Kognitif pada Soal PSAJ Mata Pelajaran Bahasa Indonesia di SMK Al-Furqon Bantarkawung - Aryanti Aryanti; Alfinatus Syahroh; Cintya Nurika Irma (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
Learning evaluation is a process of assessing the achievement of learning objectives. The research aims to determine the cognitive domain contained in the questions created by the class XII Indonesian language teacher at Al-Furqon Bantarkawung Vocational School. This research method uses qualitative methods. The data source for this research is Indonesian PSAJ questions. Data collection techniques in this research used observation, interviews, and question documents. The researcher's technical data analysis using the assessment of PSAJ questions was carried out using the cognitive domain. This cognitive domain consists of 6 levels which cover students thinking abilities from the lowest to the highest. Teachers can plan learning and determine the types of questions that suit students' abilities in analyzing Indonesian language evaluations. The cognitive domain outlines six levels of response in the thinking process, namely: The results in this study contain 6 questions, the first is knowledge, knowledge based on cognitive level indicators, the ability to name is a characteristic of category (C1), Second, comprehension, there are two questions, this question is included in comprehension, the cognitive objective of this question is the stage of understanding (C2), Third the application of data based on cognitive level indicators (C3), Fourth Analysis (analysis) the ability to explain is a characteristic of the category (C4), Fifth Synthesis: There is one data based on the question above which is included in the cognitive domain category because students are asked to combine the correct parts to make one unit (C5). The six assessments (evaluation) and one question data above are included in the category (C6), because students are asked to compare texts 1 and 2 in the analysis of Indonesian PSAJ questions.